Long term effect of cryopreservation on primary human skin cells - Ishak M.F.,; Manira M.,; Ng, Min Hwei; Khairul B.,; Gargy L.,; Aminuddin B.S.,; Ruszymah Haji Idrus, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Cryopreservation is essential for tissue engineering and regenerative medicine. This study was carried out to assess the effect of cryopreservation on skin cells and evaluate the performance of cells after 12 months of cryopreservation. Redundant skin tissue samples were obtained from surgery with consent from patients. The tissue was cleaned, processed and cultured until passage 3. Upon confluency, cells were trypsinised and total cell yield and viability were determined before and after being cryopreserved. Sterility and immunocytochemistry analysis for collagen type I (Col-1) and cytokeratin 14 (CK14) antibodies were also performed on cells cryopreserved for one, three, six and twelve months. There is no significant difference in growth rates for cryopreserved cells for 1 to 12 months, except for fibroblasts at 6 months. Cell viability for both keratinocytes and fibroblasts decreased with time (65%± 3.5% - 89%± 4.5%). Sterility testing showed no contamination after 12 months of cryopreservation. Immunocytochemistry analysis showed positive expression for CK14 (keratinocytes) and Col -1 (fibroblasts) after 12 months of cryopreservation. Morphologically, keratinocytes and fibroblasts were able to retain its phenotype. The loss in viability is consistent in all samples and possibly due to thermal-cycling effect. Immunocytochemistry and consistent cell growth analysis showed that keratinocytes and fibroblasts were able to retain their characteristics in cryopreservation condition. These preliminary findings show that primary skin cells can be stored via cryopreservation and still retain their characteristics. However, further investigations using longer periods of cryopreservation (24 months, 48 months) should be conducted.